Fire dynamics and driving mechanisms on the Eastern Coast of China since the Late Pleistocene: evidence from charcoal records on Shengshan Island - Wang, Zhigang; Wang, Cuiping; Zhang, Yao; Cheng, Yuanyu; Ren, Shaofang; Yi, Chengxin; Wang, Hui; Zhou, Limin; Qian, Peng; Zheng, Xiangmin (Frontiers in Ecology and Evolution, 2024)
Fires play a significant role in ecosystems, exerting a profound influence on climate, vegetation, and geochemical cycles, while being reciprocally affected by these factors. The reconstruction of past fire events serves as a valuable window into understanding environmental changes over time.To investigate the history of ancient fires on the Eastern Coast of China, we conducted the first charcoal analysis on a loess profile of Shengshan Island (East China Sea). Along with other biological and geochemical proxies, we successfully reconstructed the ancient fire dynamics and elucidated their driving mechanisms in this region since the late Pleistocene. Our initial findings revealed a peak in charcoal concentration during the period of 60-50 ka period, but after calibrating for sedimentation rate, the concentration significantly decreased. Fire activities remained weak during 50-30 ka, likely due to the scarcity of combustible materials. Between 30-12 ka, fires were frequent in the early period, while gradually diminishing during the later stage. Dry climate and dense vegetation likely attributed to frequent fires in early period, while some extreme events (e.g., sudden change in temperature) may have decreased the fire frequency in later period. The Holocene (began ~12 ka) evidenced the most frequent fire events as a high charcoal concentration was recorded, likely caused by human activities. After comparing our findings with other paleoecological records from surrounding areas, we confirmed the accuracy of our reconstruction of ancient fires. This reconstruction captures not only local shifts but also broader regional changes.Overall, our study highlights the importance of calibrating sedimentation rate in charcoal profiles, while also contributing to an enhanced understanding of environmental changes along the Eastern Coast of China since the Late Pleistocene.